2011
DOI: 10.5754/hge10776
|View full text |Cite
|
Sign up to set email alerts
|

HER-2/neu Assessment for Gastric Carcinoma: Validation of Scoring System

Abstract: According to high concordance rate in paired samples we consider it appropriate to evaluate HER2 expression on biopsy specimens, especially in unresectable cases, and to re-evaluate it on resected specimens if available, due to high heterogeneity of a gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Gastric cancer is the most common gastric malignant tumor and the second leading cause of death due to cancer worldwide [1, 2]. Although it is a consensus that depth of tumor invasion and number of lymph node metastasis are most intensive factors to evaluate the progression and prognosis of gastric cancer, researchers demonstrated that tumor-node-metastasis (TNM) classification was imprecise for prediction the survival of patients even in the latest version [3].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is the most common gastric malignant tumor and the second leading cause of death due to cancer worldwide [1, 2]. Although it is a consensus that depth of tumor invasion and number of lymph node metastasis are most intensive factors to evaluate the progression and prognosis of gastric cancer, researchers demonstrated that tumor-node-metastasis (TNM) classification was imprecise for prediction the survival of patients even in the latest version [3].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, only HER2 IHC 2+ or IHC 3+ were considered HER2 positive. 6 In light of the WHO's classification of digestive tumors and UICC 2010 TNM classification of malignant tumors, 20,21 the pathologist reviewed and recorded a set of histopathological parameters as follows: (1) HER2 expression status, (2) location of tumor, (3) maximum diameter of tumor, (4) differentiation degree, (5) T stage (depth of infiltration), (6) N stage (lymph node metastasis), (7) M stage (distant metastasis), (8) vascular invasion status, and (9) neural invasion status.…”
Section: Pathological Evaluationmentioning
confidence: 99%
“…4,5 In 6-35% of all GC patients, gastric lesions have been reported to over-express HER2. [6][7][8][9][10] The status of HER2 expression in gastric lesions is currently evaluated by immunohistochemistry (IHC), silver in situ hybridization (SISH), and fluorescence in situ hybridization (FISH). 5,11,12 It was found to be correlated with tumor grade and location on the intestine, but not with gender, age, tumor location or (tumor node metastasis) TNM stage, depth of invasion, lymph node metastases, and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…This scoring system is based on the intensity of reactivity, whether complete or incomplete and the percentage of reactive cells. 11,12 IHC score of 0 and 1+ was considered negative, while an IHC score of 2+ and 3+ was considered positive (Table 1). 11,13,14 Tumor cell clusters with strong complete, basolateral or lateral membranous reactivity irrespective of percentage of tumor cells stained.…”
Section: Exclusion Criteriamentioning
confidence: 99%